Population Pharmacokinetics of Imipenem in Critically Ill Patients: A Parametric and Nonparametric Model Converge on CKD-EPI Estimated Glomerular Filtration Rate as an Impactful Covariate - de Velde, Femke; de Winter, Brenda C. M.; Neely, Michael N.; Yamada, Walter M.; Koch, Birgit C. P.; Harbarth, Stephan; von Dach, Elodie; van Gelder, Teun; Huttner, Angela; Mouton, Johan W. (Clinical pharmacokinetics, 2020)
Background Population pharmacokinetic (popPK) models for antibiotics are used to improve dosing strategies and individualize dosing by therapeutic drug monitoring. Little is known about the differences in results of parametric versus nonparametric popPK models and their potential consequences in clinical practice. We developed both parametric and nonparametric models of imipenem using data from critically ill patients and compared their results. Methods Twenty-six critically ill patients treated with intravenous imipenem/cilastatin were included in this study. Median estimated glomerular filtration rate (eGFR) measured by the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation was 116 mL/min/1.73 m 2 (interquartile range 104–124) at inclusion. The usual dosing regimen was 500 mg/500 mg four times daily. On average, five imipenem levels per patient (138 levels in total) were drawn as peak, intermediate, and trough levels. Imipenem concentration-time profiles were analyzed using parametric (NONMEM 7.2) and nonparametric (Pmetrics 1.5.2) popPK software. Results For both methods, data were best described by a model with two distribution compartments and the CKD-EPI eGFR equation unadjusted for body surface area as a covariate on the elimination rate constant ( K e ). The parametric population parameter estimates were K e 0.637 h −1 (between-subject variability [BSV]: 19.0% coefficient of variation [CV]) and central distribution volume ( V c ) 29.6 L (without BSV). The nonparametric values were K e 0.681 h −1 (34.0% CV) and V c 31.1 L (42.6% CV). Conclusions Both models described imipenem popPK well; the parameter estimates were comparable and the included covariate was identical. However, estimated BSV was higher in the nonparametric model. This may have consequences for estimated exposure during dosing simulations and should be further investigated in simulation studies.